The visual culture of American religions - Morgan, David, 1957-; Promey, Sally M., 1953- (University of California Press, 2001)
Contemporary artists have often clashed with conservative American evangelicals in recent years, giving the impression that art and religion are fundamentally at odds. Yet historically, artistic images have played a profound role in American religious life.